Analysis of shrines properties using remote sensing approach: case study of Lembah Bujang - Roslan, Shairatul Akma; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Md Ali, Zuraini (Malaysian Institute of Planners, 2016)
The heritage of Lembah Bujang, Kedah is important as a starting point to understand the origins and history of civilization in Malaysia. This research is to analyze the spectral reflectance of shrines properties in an identified area by using remote sensing techniques in conserving this cultural heritage site. The remote sensing device (Spectroradiometer) was used to measure the spectral reflectance of the source of shrines in the study area. This tool was applied for reflectance’s test over properties such as ancient brick, granite, literates and iron in a different two study areas consist of Lembah Bujang and Kompleks Sungai Batu. Remote sensing test properties demonstrate that discrimination of properties types of each civilization is possible through reflection measurement, but that discrimination is complicated by surface conditions, such as weathering and lichen growth. Comparison between clays, granite and iron show that clays to be more reflective than granite and iron. This result will help more in our further study on detecting these properties direct through remote sensing imagery and will be helpful in developing new indexes and selection of threshold value on shrines material in the case study of Lembah Bujang.